Fibonacci Sequence – based FFT and DCT Performance Comparison in Audio Watermarking - Budiman, Donny; B. Suksmono, Andriyan; Danudirdjo, Donny (International Journal of Engineering and Technology, 2019)
Audio watermarking is a manner to hide watermark into the audio for copyright protection. Recently, there are many techniques based on audio watermarking. Frequency domain based audio watermarking is one of audio watermarking technique that has good watermark robustness against many attacks, good watermarked audio quality, and also high watermark payload. In this paper, FFT and DCT performance will be compared as transform technique for data hiding in audio. Host audio is first transformed into frequency domain in frame-based by FFT or DCT, then watermark is embedded into the frequency domain signal by Fibonacci sequence rule. Different than DCT which can embed watermark on full frame, in FFT, only a half of frame that can be embedded by watermark due to FFT properties. After embedding, the frequency domain signal is transformed to time domain by IFFT or IDCT to get watermarked audio. The simulation result of frequency based audio watermarking comparing FFT and DCT transform method shows that watermark payload for perfect robustness at no attack condition could reach up to 70 bps for FFT and 500 bps for DCT. With good watermarked audio quality due to ODG > -1 and SNR > 30 dB. Due to this performance, DCT is a recommended transform method for audio watermarking technique to obtain high imperceptibility, strong robustness and high capacity than FFT.Â Â